Management of dietary services at National Institute of Cancer Research and Hospital (NICRH), Bangladesh (Asian Journal of Medical and Biological Research, 2020)
Patient meals are an integral part of hospital treatment and crucial to aid recovery. A cross-sectional study was conducted to determine the Management of Dietary Services at National Institute of Cancer Research and Hospital. The purpose of this study was to make provision for safe, clean, hygienic and nutritious diet for the indoor patient as per their caloric requirement. This study compiled from 1st January to 31st December 2017 and the sample size was 113(dietary personnel 9 and patients 104) and it was purposive sampling technique. Data were collected through semi-structured questionnaire and observational check-list. Data analysis was done using SPSS software version 20. Satisfaction level was categories in to Satisfied and Dissatisfied. Among the service receiver of this hospital 15.4% were found satisfied with the dietary services. Cleanliness status of kitchen was average. It was highly suggested that the higher number of trained manpower needs to be appointed in future as required. Moreover, a standardize cooking system should be adopted by the authority for improving the quality of cooking food in order to obtain increased patient’s satisfaction.Asian J. Med. Biol. Res. September 2020, 6(3): 548-554